Clonal resistance of rubber tree to Colletotrichum spp. - Antonio, Gabriel Leonardi [UNESP]; Scaloppi Junior, Erivaldo José; Fisher, Ivan Herman; Furtado, Edson Luis [UNESP]; Firmino, Ana Carolina [UNESP] (Wiley, 2021)
The use of resistant clones of rubber trees could constitute a strategy for managing anthracnose disease caused by Colletotrichum. To examine this possibility, three isolates of Colletotrichum CH93 (C. fructicola) and CH 102 and CH 130 (C. acutatum) were used as inoculum for 20 rubber clones planted in Brazil. These evaluations took place in both a laboratory and in a clonal garden. For inoculation in the laboratory, isolates CH93 (C. fructicola) and CH102 and CH130 (C. acutatum) were used. Inoculation of the clones was performed by placing a disc of PDA with mycelium from each isolate on leaf tissues of each clone. In the clonal garden, five samples were collected at random from 30 leaflets on three different plants. In the laboratory and in the clonal garden, the percentage of leaf area damaged by the fungus was evaluated digitally. Clones had varied reactions to the different isolates used in inoculations. In the laboratory tests, clones IAC 507, IAC 502 and PR 255 appeared most resistant, with no symptoms develop, regardless of the isolate used in the inoculation. Six days after inoculation, clones PB 235, RRIM 937 and PB 311 also had low levels of disease for some fungal isolates. In field evaluations, IAC 507 and IAC 505 showed no symptoms of anthracnose. The RRIM 600 clone, which is the most cultivated, proved to be susceptible to the disease. The results provide a basis for the development of more detailed research with clone IAC 507 and with those showing less disease in the laboratory and in the field, including clones RRIM 937, IAC 505, IAC 502 and IAC 503.
Keywords: anthracnose; genetic control; Hevea brasiliensis